A qualitative longitudinal study of traumatic orthopaedic injury survivors’ experiences with pain and the long-term recovery trajectory - Olav Røise; Thomas Clausen; Leiv Arne Rosseland; Jeanette Finstad; Ingrid Amalia Havnes (BMJ Open, 2024)
Objectives To explore trauma patients’ experiences of the long-term recovery pathway during 18 months following hospital discharge.Design Longitudinal qualitative study.Setting and participants Thirteen trauma patients with injuries associated with pain that had been interviewed 6 weeks after discharge from Oslo University Hospital in Norway, were followed up with an interview 18 months postdischarge.Method The illness trajectory framework informed the data collection, with semistructured, in-depth interviews that were analysed thematically.Results Compared with the subacute phase 6 weeks postdischarge, several participants reported exacerbated mental and physical health, including increased pain during 18 months following discharge. This, andalternating periods of deteriorated health status during recovery, made the pathway unpredictable. At 18 months post-discharge, participants were coping with experiences of reduced mental and physical health and socioeconomic losses. Three main themes were identified: (1) coping with persistent pain and reduced physical function, (2) experiencing mental distress without access to mental healthcare and (3) unmet needs for follow-up care. Moreover, at 18 months postdischarge, prescribed opioids were found to be easily accessible from GPs. In addition to relieving chronic pain, motivations to use opioids were to induce sleep, reduce withdrawal symptoms and relieve mental distress.Conclusions and implications The patients’ experiences from this study establish knowledge of several challenges in the trauma population’s recovery trajectories, which may imply that subacute health status is a poor predictor of long-term outcomes. Throughout recovery, the participants struggled with physical and mental health needs without being met by the healthcare system. Therefore, it is necessary to provide long-term follow-up of trauma patients’ health status in the specialist health service based on individual needs. Additionally, to prevent long-term opioid use beyond the subacute phase, there is a need to systematically follow-up and reassess motivations and indications for continued use throughout the recovery pathway.